Assembleias de peixes de um riacho da encosta Atlântica, Brasil : estrutura espacial, uso dos recursos alimentares e relações ecomorfológicas. - Wolff, Luciano Lazzarini (2012)
This study was conducted along the longitudinal gradient of a coastal Atlantic stream, Brazil, through quarterly sampling (May/2009 to February/2010) in riffles, pools and backwaters (mesohabitats) from headwater, meddle and lowland (sample sections). The objective was to identify patterns at the spatial structure, use of feeding resources and ecomorphological relationship of the fish assemblage. We captured 29 species of which 15 were recorded at the headwater, 18 at the middle and 22 at the lowland. The richness and Shannon diversity tended to increase from the headwater to lowland, while beta diversity showed highest rates of addition rather than turnover of species along of this gradient. In addition, the structure in composition and density of the assemblage differed significantly in mesohabitat and section sample scales. Environmental differences among the mesohabitats and the increasing of the structural complexity along the gradient probably were the factors responsible for such results. The analysis of 738 stomach contents (19 species) showed that the resources more consumed were aquatic and terrestrial insects, other aquatic invertebrates and detritus/sediment. The species were organized into seven trophic guilds: detritivorous, aquatic invertivorous, terrestrial insectivorous, aquatic insectivorous, omnivorous, herbivorous and piscivorous. The composition in abundance and biomass, as well as the longitudinal distribution of guilds differed along the gradient, indicating proportional change of insectivorous species from headwater to detritivorous at the lowland, which, was possibly associated with the longitudinal availability of food resources. Three ecomorphotypes were identified: benthic species, with depressed bodies and ventral mouth, consumers of detritus and algae; nektonics, with compressed bodies and upturned or terminal mouths, consumers of plants and terrestrial invertebrates; and nektobenthics, with elongated bodies and ventrally oblique mouths, consumers of aquatic invertebrates. A classic example of ecomorphological divergence was observed between the benthic species, while others ecomorphotypes exhibited possible convergence or parallelism. Moreover, the correlations between morphology and diet were consistent with the functional interpretations, while other factors beyond the morphology weakened the relations between morphology and habitat use.